Comparative Evaluation of Fluoride Recharge Ability of Conventional and Hydroxyapatite Modified Glass Ionomer Cement with Daily Low Fluoride Exposure- An Invitro Study - Panigrahi, Antarmayee (J Clin Diagn Res, 2016)
INTRODUCTION: Glass ionomer cement (GIC) has best suited paediatric dentists and is well recognised in the preventive era of dentistry. However its use is affected by its inferior mechanical properties. Hydroxyapatite whiskers have been lately introduced as strengthening additive without affecting its fluoride releasing property, but literature lacks data related to its effect on recharging ability of glass ionomer cement. AIM: To evaluate and compare fluoride release from hydroxyapatite incorporated glass ionomer cement following recharging with low fluoride dentifrices. MATERIALS AND METHODS: An 8% Hydroxyapatite whiskers were added to Conventional Glass ionomer powder and 40 specimens each of conventional and Hydroxyapatite Glass ionomer cement were prepared using customised Teflon mould (5mm x 2mm) and were suspended in deionised water. Recharging of aged specimens was done using low fluoridated dentifrices containing 500ppm fluoride, twice daily and water was replenished every 24 hours. Fluoride release was analysed daily for 7 days and then weekly till 21 days using Sension 4 pH/ion selective electrode. Data thus obtained was statistically analysed by descriptive analysis followed by repeated measures ANOVA. RESULTS: Significant (p<0.01) increase in fluoride release was observed in both the materials following recharging regimen. Recharge pattern of hydroxyapatite glass ionomer was found to be similar to conventional glass ionomer cement. CONCLUSION: Within the limitations of this study it can be evinced that fluoride rechargability and re-release remains unaffected by the addition of hydroxyapatite whiskers and hence proves to be more acceptable additive to glass ionomer cement to improve its mechanical properties widening its arena of usage by clinicians.